Impedance spectroscopy studies on PbFe0.5Nb0.5O3 –BiFeO3 multiferroic solid solution. Issue 18 (15th December 2017) - Dadami, Sunanda T.; Matteppanavar, Shidaling; I, Shivaraja; Rayaprol, Sudhindra; Deshpande, S.K.; Murugendrappa, M.V.; Angadi, Basavaraj
Abstract: (1-x) PbFe0.5 Nb0.5 O3 (PFN) – (x) BiFeO3 (BFO) (PFN – BFO) multiferroic solid solution (x = 0.1, 0.2, 0.3 and 0.4) were synthesized by single step solid state reaction method. Single phase was confirmed in all the samples through room temperature (RT) X-ray Diffraction (XRD) with monoclinic structure ( Cm space group). Transmission Electron Microscopy (TEM) studies confirm the high crystallinity of the materials with the average particle size of 100 nm. The temperature (313–528 K) and frequency (100 Hz – 5 MHz) dependent impedance, modulus and DC conductivity of PFN – BFO solid solutions were investigated. An impedance spectroscopy result shows a significant contribution from the grains (bulk) to the conductivity and exhibits non-Debye type of relaxation. The bulk (grain) resistance reduces as the temperature increases corresponds to negative temperature coefficient of resistance (NTCR) behaviour. Electric modulus exhibits thermally dependent relaxation phenomena in the material. The Bergmann modified KWW function fitted to the imaginary modulus with non-Debye type of relaxation. DC conductivity of PFN – BFO solid solutions was found to follow the Arrhenius behaviour.